Relationship between Occupational Fatigue and Sleep Quality among Nurses of Teaching Hospitals in Golestan University of Medical Sciences - Alireza Heidari; Shamim Imani Gorgi; Farideh Koochak; Zahra Khatirnamani (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: Nurses' fatigue is defined as a mental and multidimensional feeling of fatigue that is physically and mentally penetrating and may even remain despite periods of rest. In addition to fatigue, nurses suffer from lack of sleep and its poor quality more than other occupational groups. This study was conducted to determine the relationship between occupational fatigue and sleep quality in nurses. Methods: This was a correlational and cross-sectional descriptive study that was conducted at Golestan University of Medical Sciences, Golestan, in 2021. A total of 277 nurses were included in the study after random stratified sampling and obtaining the code of ethics. The required data were collected by Swedish Occupational Fatigue Inventory and Pittsburgh Sleep Quality Index, and analyzed in SPSS-23 software using descriptive statistics and Spearman correlation, Mann-Whitney, and Kruskal-Wallis tests. Results: The mean scores of the nurses' age and work experience were obtained at 28.75 ± 4.8 years and 5.66 ± 4.6 years, respectively. In total, 68.6% of the nurses were women. The mean of the total occupational fatigue score was 53.18 ± 22.5, which was evaluated at a lower-than-average level. The mean of nurses' sleep quality was 18.14 ± 1.77, which indicated poor sleep quality in nurses. There was an inverse and significant relationship between the score of occupational fatigue and all its dimensions and sleep quality. Conclusion: The level of occupational fatigue in nurses was lower than the average and their sleep quality was poor, and with the increase in occupational fatigue, the quality of sleep decreased. It is suggested to implement individual and organizational solutions to reduce and eliminate occupational fatigue and improve sleep quality.